Procedimientos de ortodoncia mecánicos y no mecánicos en recaída y retención: revisión de cobertura temática (2020)
Stability after orthodontic treatment is an important goal for orthodontists. This issue has been highly important in orthodontics, so its progress and content require constant analysis.